PROCEDURAL RIGHTS OF SUSPECTS AND ACCUSED PERSONS DURING PRE-TRIAL DETENTION – IMPACT OF DETENTION CONDITIONS ON EFFICIENT EXERCISE OF DEFENCE RIGHTS (EU and comparative law issues and challenges series (ECLIC), 2020)
The paper analyses the possibilities of detainees to effectively exercise their defence rights during the pre- trial detention. Deprivation of liberty presupposes limited abilities of detainees to move and to take actions and, consequently, it may affect their possibilities to exercise the rights guaranteed by the law. Hence, a correlation between material conditions of detention and defence rights can be perceived. Inadequate detention conditions, in addition to leading to inhuman and degrading treatment, can also pose an obstacle for the full enjoyment of procedural rights, primarily the right of access to a lawyer, the right to have adequate time and facilities for the preparation of defence. In this regard, detention conditions can lead to the violation of the right to a fair trial. On the other hand, effective exercise of the right to access to a lawyer is one of the most important guarantees of protection against torture, inhuman and degrading treatment during detention. Therefore it is necessary not only to legally prescribe the special procedural guarantees for suspects and accused deprived of their liberty but also to provide such material conditions, which are often limited and insufficient within the prison systems, for the enforcement of the pre-trial detention in a way which will enable the full and efficient exercise of the defence rights guaranteed by the law. In the paper, the author analyses the procedural guarantees for detainees which are enshrined within the EU directives on procedural rights of suspects and accused persons and the ECtHR case law in the light of detention conditions. Special attention in paper has been given to the Croatian law and an assessment of the procedural rights and detention conditions in pre-trial detention within the national legal framework and case law.